Esejistika Ivana Cankarja - Štuhec, Miran (Slavistična revija, 2006)
Ivan Cankar occupies a special place in Slovene cultural awareness. His work had drawn the attention of his contemporaries and Slovene literary criticism always showed particular interest in it. In his very extensive opus that includes poetry, narrative prose, and drama, a prominent place is occupied by publicistic writing, i. e., political articles, essays, published speeches, critics, and polemics. Without a doubt, this is an important corpus, with which the author responded to many very and sometimes less buming issues of his time. They were typically related to historical, political, national, and cultural topics, in the nexus of which we sooner or later find Slovene literature and art.
Keywords: Cankar, Ivan, 1876-1918; criticism; esej; essay; essay writing; intellectual prose; književna esejistika; kritičnost; literary essay; miselna proza; polemicism; polemičnost; satiricism; satiričnost; Slovene literature; slovenska književnost